Memory impairment induced by IL-1beta is reversed by alpha-MSH through central melanocortin-4 receptors - Gonzalez, Patricia Verónica (2009)
Interleukin-1beta (IL-1beta) significantly influences memory consolidation. Treatments that raise the level of IL-1beta in the brain, given after training, impair contextual fear conditioning. The melanocortin alpha-MSH exerts potent anti-inflammatory actions by physiologically antagonizing the effect of pro-inflammatory cytokines. Five subtypes of melanocortin receptors (MC1R-MC5R) have been identified, with MC3R and MC4R predominating in the central nervous system. The present experiments show that injection of IL-1beta (5ng/0.25mul) in dorsal hippocampus up to 15min after training decreased freezing during the contextual fear test. The treatment with IL-1beta (5ng/0.25mul) 12h after conditioning cause amnesia when animals were tested 7days post training. Thus, our results also demonstrated that IL-1beta can influence persistence of long-term memory. We determined that animals previously injected with IL-1beta can acquire a new contextual fear memory, demonstrating that the hippocampus was not damaged. Treatment with alpha-MSH (0.05mug/0.25mul) blocked the effect of IL-1beta on contextual fear memory. Administration of the MC4 receptor antagonist HS014 (0.5mug/0.25mul) reversed the effect of alpha-MSH. However, treatment with gamma-MSH (0.5mug/0.25mul), an MC3 agonist, did not affect IL-1beta-induced impairment of memory consolidation. These results suggest that alpha-MSH, through central MC4R can inhibit the effect of IL-1beta on memory consolidation.